Achieving great optical anisotropy with the well-directed alignment of π-conjugated groups due to hydrogen bonds - Chenhui Hu (Journal of Saudi Chemical Society, 2024)
Looking for novel UV birefringent units with great birefringence and discovering new candidates that are constructed by them have always been a hotspot in the field of optical materials. Here, a new imidazole-based [C3N2H5]2C2O4·H2O crystal is synthesized with a cutoff edge (274 nm). According to achieve the well-directed alignment, the millimeter-sized single crystal [C3N2H5]HC2O4 is obtained and possesses a larger birefringence than [C3N2H5]2C2O4·H2O with a similar band gap. What’s more, the [C3N2H5]HC2O4 crystals can be grown by a simple aqueous solution volatilization method, and the difference in the measured refractive index of [C3N2H5]HC2O4 is 0.119@546 nm which is similar to the birefringence of the famous α-BBO crystal. The birefringence originates from the π-conjugated [C3N2H5] units and [HC2O4] units, which implies [C3N2H5]HC2O4 is promising candidates for exploring UV materials with large birefringence.